Gouvernorat Kafr esch-Scheich, Ägypten. Landschaftsarchäologie und regionale Siedlungsnetzwerke um den Fundplatz Tell el-Faraʿin (Buto) im Nildelta - Schiestl, Robert (e-Forschungsberichte des DAI, 2017)
The season 2015 focused on the reconstruction of the ancient landscape in the northwestern Nile Delta by means of auger core drillings. In particular, two questions were addressed: Firstly, was there an ancient branch of the Nile flowing roughly in the area of two modern canals? This seemed to be indicated by the linear distribution of settlements, predominantly of the Roman and Late Roman age. Secondly, what is the precise extent of an ancient lagoon, which was first identified by the discovery of peat layers in the 1980s?